Implementation of Hypnoteaching Principles in Learning Indonesian Text Writing Merdeka Curriculum: Literature Review - Didin Widyartono; Imam Agus Basuki; Laili Ivana (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
Writing skills are one of the important aspects in Indonesian language learning that significantly contribute to developing students' critical, logical, and creative thinking skills. However, students often perceive learning to write as problematic and boring, so their motivation and engagement in the learning process tend to be low. Therefore, an innovative approach is needed to overcome these challenges. This research aims to explore the implementation of hypnotherapy principles in learning to write Indonesian texts, particularly in the context of the Merdeka Curriculum. Hypnotaching is a teaching method that utilises techniques of positive suggestion, pacing, leading, modelling, relaxation, alpha state, and visualisation to increase students' motivation and engagement in the learning process. The method used in this research is a literature study. Various theoretical sources and previous research were analysed to identify how hypnotherapy techniques can be effectively applied in learning to write fiction and nonfiction. The results show that applying hypnotherapy principles can effectively support the objectives of the Merdeka Curriculum, which focuses on developing students' creativity and critical thinking skills in writing Indonesian texts. The application of Hypnotaching Techniques (such as positive suggestion, visualisation, and modelling) effectively supports the objectives of the Merdeka Curriculum, which focuses on developing students' creativity and critical thinking skills in writing texts. Thus, hypnoteaching principles can be an innovative and practical approach in learning writing in secondary schools, providing students with space to experiment, develop new ideas, and improve the overall quality of their writing.